Comparison of the two different protocols for biosecurity assessment in commercial pig farms - Branko Angjelovski ,Vanja Kondratenko, Milenko Simovikj, Jovan Bojkovski Miroslav Kjosevski (University Ss Cyril and Methodius, Faculty of veterinary medicine, Lazar Pop – Trajkov 5-7, 1000 Skopje, Macedonia, 2022)
Biosecurity is one of the most important aspects concerning animal health in pig farms. It is associated with measures and actions taken on the farm to reduce the risk of entering and spreading infectious diseases. There are many different protocols for biosecurity assessment in pig farms. Biocheck.UGenttm is the most commonly used biosecurity protocol, while the biosecurity of Macedonian pig farms is assessed by the protocol implemented by the Macedonian Food Veterinary Agency (FVA). The objective of this study was to compare and identify differences between the two different protocols for biosecurity assessment in commercial pig farms. Thirteen farrow-to-finish commercial pig farms were included in the study. The mean number of sows in the herds was 364 (range 50 to 1550). The biosecurity level of the herds was assessed by both Biocheck.UGenttm scoring system and “score index” system for biosecurity assessment adopted by the FVA. The two assessment protocols were synchronized for score comparison. Descriptive statistical analysis (Mean, SD) was used for the data obtained by both biosecurity protocols, and mean scores were compared by non-parametric tests. Total scores on farm level gained from protocols were subjected to non-parametric correlation analyses. The level of agreement between both protocols was also calculated. The mean synchronized biosecurity score was detected by Biocheck.UGenttm for all farms was 44.6± 13.4 (range 19 to 64), while 32.4 ±3.8 score (range 26.4 to 40.45) was obtained by the “score index” system. A significant difference (p=0.006) between the mean scores of both protocols was found. Regarding farm categorization, according to the “score index” system developed by FVA, 92.3% of the farms were considered with low biosecurity risk and one farm had medium biosecurity risk. In contrast to the categorization based on the Biocheck.UGenttm38.5 % farms were classified as low biosecurity risk category and 61.5% of the farms belonged to the medium biosecurity risk category. The level of biosecurity agreement between the two scoring systems was 46%. Correlations analysis gave a low non-significant correlation between total farm scores obtained by the two assessment protocols (Spearman R=0.36; p=0.23). The results of this study indicate significant differences between scores detected by two biosecurity protocols. In addition, Biocheck.UGenttm has higher and more rigorous criteria for biosecurity assessment compared to the FVA protocol due to the more detailed approach during evaluation.
Keywords: biosecurity assessment, pig farm, protocol